Calculus / With Analytic Geometry: Second Edition - Zill Dennis G (Pws-Kent Publishing Company, 1988)
Function, Limits of Functions, The Derivative, Applications of the Derivative, The Integral, Applications of the Integral, Inverse Trigonometric Functions, Logarithmic and Exponential Functions, Techniques of Integration, Indeterminate Forms and Improper Integrals, Sequences and Series, Analytic Geometry in the Plane, Parametric Equations and Polar Coordinates, Vectors and 3-Space, Vector Valued Functions, Differential Calculus of Functions of Several Variables, Multiple Integrals, Vector Integral Calculus, Differential Equations, Appendices, Index.